2022
DOI: 10.1186/s13034-022-00529-z
|View full text |Cite
|
Sign up to set email alerts
|

The importance of familial risk factors in children with ADHD: direct and indirect effects of family adversity, parental psychopathology and parenting practices on externalizing symptoms

Abstract: Background Children experiencing unfavorable family circumstances have an increased risk of developing externalizing symptoms. The present study examines the direct, indirect and total effects of family adversity, parental psychopathology, and positive and negative parenting practices on symptoms of attention-deficit/hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) in children with ADHD. Methods Data from 555 children (M = 8.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…In conclusion, the presence of maltreatment in children with ADHD is associated with some psychosocial factors such as domestic violence, peer discord, problematic family communication, and dysfunctional family functioning. Family adversity, parental psychopathology, and negative parental attitudes are associated with ADHD and ODD, for which routine questioning is recommended 40 . In these cases, interventions that will improve family functions should also be considered in the multimodal treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the presence of maltreatment in children with ADHD is associated with some psychosocial factors such as domestic violence, peer discord, problematic family communication, and dysfunctional family functioning. Family adversity, parental psychopathology, and negative parental attitudes are associated with ADHD and ODD, for which routine questioning is recommended 40 . In these cases, interventions that will improve family functions should also be considered in the multimodal treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other factors such as parent psychopathology also attributed to offspring ADHD. Previous studies reported that the likelihood of ADHD was higher among children whose parents were diagnosed with psychiatric disorders [ 9 , 10 ], which further reduces the neurocognitive performance of children with ADHD [ 11 ]. This implies that children whose parents with psychopathological symptoms should be screened for ADHD and incorporated into treatment programs.…”
Section: Introductionsmentioning
confidence: 99%